CONSIDERATIONS REGARDING DEFECTS THAT MAY OCCUR DURING FSP/SFSP PROCESSING OF ALUMINUM ALLOYS (Nonconventional Technologies Review, 2025)
The paper provides a comprehensive analysis of the defect phenomena associated with friction stir processing (FSP) and submerged friction stir processing (SFSP) of aluminium alloys. The investigation systematically addresses the origins, typologies, and implications of both surface and internal defects observed in rolled and cast aluminium alloys subjected to these advanced solid-state processing techniques. Key factors influencing defect formation, including tool geometry, process parameters, intrinsic material characteristics, and environmental conditions, are critically examined. The review further delineates material-specific responses to FSP/SFSP and highlights the challenges posed by initial microstructural inhomogeneities and compositional variations. Strategies for defect prevention are discussed, emphasizing the importance of optimized tool design, precise process control, and the integration of post-processing treatments. The findings underscore the necessity of a multidisciplinary approach - encompassing rigorous material pre-characterization, controlled processing environments, and adaptive monitoring systems - to ensure structural integrity and enhanced mechanical performance of processed components. This work advances the understanding of defect mechanisms in FSP/SFSP and offers evidence-based guidelines for the production of high-quality, high-performance aluminium alloy components suitable for demanding engineering applications.
Keywords: FSP; SFSP; causes of defects; rolled aluminium alloys; cast aluminium alloys